ANALISIS PERAN BUDAYA ORGANISASI DAN KINERJA PEGAWAI MEALLUI KOMUNIKASI KERJA PADA KANTOR KECAMATAN TAMALANREA KOTA MAKASSAR - Hendra Gunawan (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2024)
This study aims to analyze the effect of organizational culture on employee performance, both directly and indirectly through work communication at the Tamalanrea District Office, Makassar City. This study employed a quantitative approach with an explanatory research design. The research population consisted of all employees of the Tamalanrea District Office, with a total of 141 respondents. Data were collected through questionnaires and analyzed using Partial Least Squares Structural Equation Modeling. The results indicate that organizational culture has a positive and significant effect on work communication. Organizational culture also has a positive and significant effect on employee performance. Furthermore, workplace communication has been shown to have a positive and significant effect on employee performance. The mediation test demonstrates that work communication significantly mediates the effect of organizational culture on employee performance. These findings confirm that employee performance is determined not only by a strong organizational culture but also by the effectiveness of work communication in translating organizational values into actual work behavior. This study implies that strengthening organizational culture, accompanied by improving work communication, is an important strategy for enhancing employee performance in public sector organizations.